Rapid strain accumulation on the Ashkabad fault (Turkmenistan) from atmosphere‐corrected InSAR. Issue 7 (1st July 2013) - Walters, R. J.; Elliott, J. R.; Li, Z.; Parsons, B.
<x xml:space="preserve">Abstract</x> [1] We have measured interseismic deformation across the Ashkabad strike‐slip fault using 13 Envisat interferograms covering a total effective timespan of ∼30 years. Atmospheric contributions to phase delay are significant and variable due to the close proximity of the Caspian Sea. In order to retrieve the pattern of strain accumulation, we show it is necessary to use data from Envisat's Medium‐Resolution Imaging Spectrometer (MERIS) instrument, as well as numerical weather model outputs from the European Centre for Medium‐Range Weather Forecasts (ECMWF), to correct interferograms for differences in water vapor and atmospheric pressure, respectively. This has enabled us to robustly estimate the slip rate and locking depth for the Ashkabad fault using a simple elastic dislocation model. Our data are consistent with a slip rate of 5–12 mm/yr below a locking depth of 5.5–17 km for the Ashkabad fault, and synthetic tests support the magnitude of the uncertainties on these estimates. Our estimate of slip rate is 1.25–6 times higher than some previous geodetic estimates, with implications for both seismic hazard and regional tectonics, in particular supporting fast relative motion between the South Caspian Block and Eurasia. This result reinforces the importance of correcting for atmospheric contributions to interferometric phase for small strain measurements. We also attempt to validate a recent method for atmospheric correction based on ECMWF ERA‐Interim model outputs alone and find that this technique does not work satisfactorily for this region when compared to the independent MERIS estimates.